2008
DOI: 10.1016/j.schres.2008.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Differential association of the COMT Val158Met polymorphism with clinical phenotypes in schizophrenia and bipolar disorder

Abstract: Schizophrenia and bipolar disorder, although diagnostically separate, likely share elements of their genetic etiology. This study assessed whether COMT Val158Met polymorphism has shared or specific associations with clinical phenotypes evident in schizophrenia and bipolar disorder. Schizophrenia and bipolar patients completed a clinical assessment encompassing premorbid functioning and current and lifetime symptomatology. Multivariate analyses yielded a three-way interaction of diagnosis, COMT genotype, and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 26 publications
9
32
0
1
Order By: Relevance
“…Additionally, evidence suggests that prefrontal dopamine plays a critical role in the normal cognitive process, especially in working memory, planning and attention (Seamans and Yang, 2004). Some studies have found that dysfunctions in prefrontal DA may underlie neuropsychiatric pathologies, such as the cognitive deficits associated with schizophrenia and bipolar disorder (Egan et al, 2001;Seamans and Yang, 2004;Tunbridge et al, 2006;Goghari and Sponheim, 2008). Moreover, one recent study suggests a reciprocal interplay between working memory capacity and cortical dopamine neurotransmission (McNab et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evidence suggests that prefrontal dopamine plays a critical role in the normal cognitive process, especially in working memory, planning and attention (Seamans and Yang, 2004). Some studies have found that dysfunctions in prefrontal DA may underlie neuropsychiatric pathologies, such as the cognitive deficits associated with schizophrenia and bipolar disorder (Egan et al, 2001;Seamans and Yang, 2004;Tunbridge et al, 2006;Goghari and Sponheim, 2008). Moreover, one recent study suggests a reciprocal interplay between working memory capacity and cortical dopamine neurotransmission (McNab et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have implicated the genes coding for the catechol-O-methyltransferase (COMT ) enzyme, brain-derived neurotrophic factor (BDNF ) and notably neuregulin 1 (NRG1) as candidate genes for schizophrenia (Li et al 1996 ;Egan et al 2001 ;Shifman et al 2002Shifman et al , 2004Glatt et al 2003 ;Handoko et al 2005 ;Lohoff et al 2005 ;Owen et al 2005 ;Chen et al 2006 ;Jonsson et al 2006 ;Ehlis et al 2007 ;Goghari & Sponheim, 2008 ;Okochi et al 2009 ;Zhang et al 2009). There is also a large body of evidence demonstrating the inconsistency of association between polymorphisms in COMT, BDNF and NRG1 genes and psychotic disorders in samples across the globe (Munafo et al 2005 ;Prata et al 2006 ;Kanazawa et al 2007 ;Ikeda et al 2008 ;Sanders et al 2008 ;Jonsson et al 2009 ;Kawashima et al 2009 ;Okochi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have identified an association between SZ and the Val158 allele [Li et al, 1996;de Chaldee et al, 1999;Egan et al, 2001;Kremer et al, 2003;Wonodi et al, 2003;Abdolmaleky et al, 2006;Goghari and Sponheim, 2008], although the last meta-analyses have brought about negative results [Fan et al, 2005;Munafo et al, 2005]. Strongest evidences of a significant association between the COMT Val158 allele gene and SZ have been observed in haplotype studies [Shifman et al, 2002;Sanders et al, 2005].…”
Section: Introductionmentioning
confidence: 99%